Derivation of Clinically Applicable Schwann Cells from Bone Marrow Stromal Cells for Neural Repair and Regeneration - Cai, Sa; K.H. Shea, Graham; Y.P. Tsui, Alex; Chan, Ying-Shing; K.Y. Shum, Daisy (CNS & Neurological Disorders - Drug Targets, 2011)
Schwann cells are critically important for tissue repair, axonal regrowth and remyelination following injury to peripheral nerves. The absence of Schwann cells or an equivalent cell type in the central nervous system (CNS) may limit the regeneration capacity of the CNS. Mesenchymal stem cells (MSCs) have therefore been investigated for their potential to be induced to develop a Schwann cell phenotype. The methods for derivation of Schwann cell-like cells from MSCs and the benefits and limitations of each of these methods are presented in this review. Issues related to instability of the derived Schwann cell phenotype, apoptosis of derived cells in transplants, and the inability to predict with confidence how the cells will behave after transplantation are discussed. Finally, we suggest the need for further elucidation of the biology of Schwann cell differentiation and the signals for their derivation from MSC, in order to resolve these obstacles and to enable transplantation of MSC-derived Schwann cells as a therapeutic strategy in CNS injury.
Keywords: stem cell co-culture